Nucleic acids and analogs for bone regeneration. (December 2018) - Zhang, Yuxin; Ma, Wenjuan; Zhan, Yuxi; Mao, Chenchen; Shao, Xiaoru; Xie, Xueping; Wei, Xiawei; Lin, Yunfeng
Abstract With the incidence of different bone diseases increasing, effective therapies are needed that coordinate a combination of various technologies and biological materials. Bone tissue engineering has also been considered as a promising strategy to repair various bone defects. Therefore, different biological materials that can promote stem cell proliferation, migration, and osteoblastic differentiation to accelerate bone tissue regeneration and repair have also become the focus of research in multiple fields. Stem cell therapy, biomaterial scaffolds, and biological growth factors have shown potential for bone tissue engineering; however, off-target effects and cytotoxicity have limited their clinical use. The application of nucleic acids (deoxyribonucleic acid or ribonucleic acid) and nucleic acid analogs (peptide nucleic acids or locked nucleic acids), which are designed based on foreign genes or with special structures, can be taken up by target cells to exert different effects such as modulating protein expression, replacing a missing gene, or targeting specific gens or proteins. Due to some drawbacks, nucleic acids and nucleic acid analogs are combined with various delivery systems to exert enhanced effects, but current studies of these molecules have not yet satisfied clinical requirements. In-depth studies of nucleic acid or nucleic acid analog delivery systems have been performed, with a particular focus on bone tissue regeneration and repair. In this review, we mainly introduce delivery systems for nucleic acids and nucleic acid analogs and their applications in bone repair and regeneration. At the same time, the application of conventional scaffold materials for the delivery of nucleic acids and nucleic acid analogs is also discussed. Bone Regeneration: Nucleic acids and analogs in bone repair Used with an appropriate delivery system, nucleic acids and nucleic acid analogs have excellent potential for bone repair and regeneration. Owing to various challenges with bone tissue regeneration, current research is largely focused on gene therapy, which employs genes to treat or prevent disease, and such new materials as nucleic acids (DNA and RNA) and nucleic acid analogs (compounds structurally similar to naturally occurring nucleic acids). A team headed by Yunfeng Lin at Sichuan University, China conducted a review of delivery systems for nucleic acids and nucleic acid analogs and their application in bone repair and regeneration. The authors identified the use of biomaterial scaffolds (which mimic living tissue) as one of the most important research areas for gene therapy, and that strategy has proven effective with all types of bone regeneration and repair.